Analysis Interaction of Immunoglobulin G and Immunoglobulin A Against PstS1 as a Basis Specimen Selection for M. tuberculosis Rapid Test Diagnostic Agent - Rahmadani, Nabila -; Raras, Tri Yudani Mardining; Arthamin, Maimun Zulhaidah (Journal of Biomedicine and Translational Research, 2023)
Background: The recombinant Ag38 protein developed from a local strain of Mycobacterium tuberculosis has great potential to be used as a sero-diagnosis agent using the antigen rapid test because it has several epitopes that bind to antibodies. However, it is not yet known which antibody Ag38-recombinant binds maximally between IgA and IgG.Objective: The aim of this study is to compare the interaction between IgG and IgA on Ag-38 rec in silico as a basis for the selection of sero-diagnosis agents in the TB rapid test.Methods: The results show that the protein PstS1 has a higher binding sensitivity to IgG based on one of the docking models which shows a docking score of -229.70, a confident score of 0.8312 and RMSD 1.060 A. The ramachandran plot also shows that testing on this model has a protein structure that is good, with disallowed regions [X,X] values of 0.5% (less than 0.8%). The results of this analysis show that the most favored regions are 90.5% with a G-factor of -0.27. The quality of the structure of the 3D mooring model can be said to be good because it fulfills the ideal structure requirements.Conclusion: Ag38-rec antigen M. tuberculosis H37Rv binds to IgG more strongly than IgA.